Correlates of High HIV Viral Load and Antiretroviral Therapy Adherence Among Viremic Youth in the United States Enrolled in an Adherence Improvement Intervention - Amico, K. Rivet (AIDS Patient Care STDS, 2021)
A sizable portion of youth (ages 13–24) living with HIV in the United States have unsuppressed viral load. The AIDS Interventions (ATN) 152 study [evaluating the Triggered Escalating Real-Time Adherence (TERA) intervention] baseline data were examined to identify correlates of high viremia (>5000 copies/mL) and self-reported adherence, which can help in planning of differentiated services for viremic youth. Depression, HIV-stigma, and cannabis use were common in this sample of 87 youth. Almost half (48%) had high viremia, which associated with enacted stigma, moderate- to high-risk alcohol use, mental health diagnosis, and age ≥21. Self-reported adherence was related to viral load and associated with mental and physical health functioning, depression, social support, self-confident decision-making, total and internalized stigma, adherence motivation, and report of a missed a care visit in the past 6 months. Mental health emerged as a common correlate of viral load and adherence. Clinical Trial Registration number: NCT03292432.